A New Real-Life Test for Reciprocity in Autistic Adults: The Interactive Drawing Test - Backer van Ommeren, Tineke; Vreugdenhil, Marianne; Koot, Hans M.; Spek, Annelies; Scheeren, Anke M.; Jertberg, Robert M; Begeer, Sander (Frontiers in Psychiatry, 2022)
Impaired social-emotional reciprocity is a defining feature of Autism Spectrum Disorder (ASD). Deficits in reciprocity can be difficult to assess, particularly in adults with average or above average intelligence. The recently developed Interactive Drawing Test (IDT) measures reciprocity in children and adolescents with and without ASD based on spontaneous non-verbal interactions during the joint creation of a drawing. In this study, we examined if the IDT is able to differentiate between 19 normally intelligent adults with ASD and 18 without ASD. The IDT total reciprocity score, including the number of meaningful contributions to objects initially drawn by the examiner, was lower in the autistic adults compared to those without ASD. By assessing both the quantity and quality of spontaneous reciprocal behavior, the IDT was able to identify subtle differences in reciprocal behavior of adults with and without ASD with average intelligence. Even though a larger sample is required to determine its psychometric properties, the IDT appears a promising tool to enrich the diagnostic process of ASD in adults. Impaired social-emotional reciprocity is a defining feature of Autism Spectrum Disorder (ASD). The clinical field lacks sensitive tests for assessing impaired reciprocity. The recently developed Interactive Drawing Test (IDT) for reciprocity was tested in autistic and non-autistic adults. During the IDT, an examiner and participant make a joint drawing, taking turns, without specifying what they will draw. We aimed to investigated whether autistic adults showed less reciprocal behavior on the IDT compared to non-autistic participants. Autistic participants were less likely to jointly draw with the examiner, in particular when the examiner initiated a topic. The IDT revealed subtle but characteristic differences in reciprocal behavior related to ASD, suggesting it may be a promising diagnostic tool.